The Development of Quranic Reading Skills Using AR book for Primary School Students, year 4 - Deng, Abdularsi (Al-HIKMAH Journal, 2021)
The objectives of this research were (1) to develop and examine the efficiency of Quranic reading skills using AR book for primary school students, year 4 efficiency criteria 80/80 (2) to compare students’ achievement between before instruction and after instruction by Quranic reading skills using AR book (3) to evaluate students’ satisfaction towards instruction by Quranic reading skills using AR book. The participants were 20 primary school students, year 4 of Thung Yang Daeng Pittayakom School. The research instruments were (1) lesson plans (2) achievement test and (3) questionnaires on students’ satisfaction towards instruction by Quranic reading skills using AR book. The data was collected by using quasi-experimental research form namely one group pre-test and post-test design. The data was analyzed by percentage, mean, standard deviation and t-test.